(untitled) (Philologia, 2021)
The person as a grammatical category is primarily connected with verb forms and pronouns. In the Japanese language, however, verbs generally do not conjugate according to person, and personal pronouns, whenever possible, are avoided. Therefore the Japanese language is considered to express category of person very weakly, if at all. Nevertheless, there are certain verbs (e.g. くれる, やる, あげる etc.) and adjectives (e.g. そうだ, たい etc.) which differ depending on the person they refer to, and they are in the focus of this paper.